Millennial Santris’ Comprehension of Sundanese Hadith Texts: A Study at Pondok Pesantren Al-Mardhiyyah Al-Islamiyyah, Bandung - Dadah Dadah (UIN Sunan Gunung Djati Bandung, 2025)
Cultural linguistic shifts in the era of globalization have led to a degradation of mother tongue proficiency among the millennial generation, including Sundanese santri. This phenomenon poses a challenge for traditional pesantren in West Java that maintain a curriculum of Sundanese-based Hadith studies. This study aims to evaluate the comprehension level of millennial santri regarding Sundanese Hadith texts and to identify the lexical barriers encountered. The research was conducted at Pondok Pesantren Al-Mardhiyyatul Islamiyyah, Bandung Regency, employing a descriptive qualitative method. Data collection instruments included participatory observation and vocabulary comprehension tests administered to 20 millennial santri, utilizing Hadith samples on the theme of thaharah (purification) from the book Papadang Ati. The results indicate that while santri generally grasp the context of the Hadith, there exists a 21% lexical comprehension gap; students struggled to understand archaic Sundanese terms (buhun) such as lingsemeun, mopoyankeun, and pancaindra. These findings suggest a need for the revitalization of kitab kuning instructional methods that prioritize not only Sharia content but also the preservation of local linguistics.